Customer Priority Assessment in Freight Forwarding Services: A SMART Method Application in the Context of Halal Ecosystem - Evitha, Yuli; Vikaliana, Resista; Raja Zuraidah Raja Mohd Rasi (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article discusses evaluating customer priorities in freight forwarding companies using the Simple Multi-Attribute Rating Technique (SMART). SMART techniques can be used to evaluate consumer priorities within an organisation, taking into account factors such as delivery timeliness, the safety and integrity of goods, communication and response, pricing, and flexibility in service options. This study seeks to identify and assess the service features that consumers consider most significant and offer recommendations for service improvement. The results revealed that the A2 alternative was rated first, A1 second, and A6 third, with scores of 0.547, 0.257, and 0.185667, respectively, underscoring a preference for traits with greater benefits. Customers prioritise the safety and integrity of the goods, achieving a maximum score of 76, indicating a significant assessment of the condition of the goods received. This is especially relevant in the halal ecosystem, where compliance with halal standards is essential across sectors such as food, pharmaceuticals, and cosmetics. The transportation and management of halal-certified products must comply with halal certification standards, which quickly impacts consumer choice in the freight forwarding industry. Damage or loss of goods during delivery is a significant issue that the service provider must address. Investigations show that customers prioritise reliability, security, integrity of goods, speed of delivery, and effective communication, which is further strengthened by the increasing demand for halal-compliant services.